Life in green: Associations between greenspace availability and mental health over the lifecourse – A 40-year prospective birth cohort study - B. Deng; J. Boden; N. Ye; J. Morgenroth; M. Campbell; P. Eggleton; G. McLeod; M. Hobbs (Environment International)
Background: The beneficial impacts of greenspace availability on mental health are well-documented. However, longitudinal evidence using a spatial lifecourse perspective is rare, leaving the dynamics of how greenspace influences mental health across the lifecourse unclear. This study first uses prospective birth cohort data to examine the associations between greenspace availability in childhood (0–16 years) and mental health in adolescence (16 years) and between greenspace availability and mental health across adulthood (18–40 years). Method: Data were obtained from the Christchurch Health and Development Study, comprised 1,265 cohort members born in Christchurch, New Zealand, in 1977. Mental health outcomes including depressive symptoms, anxiety disorders and suicidal ideation were assessed in adolescence (16 years), and in adulthood (18–40 years). Greenspace availability from birth to age 40 years was measured as the proportion of vegetated areas within circular buffers (radius from 100m to 3000m) around members’ geocoded residential addresses using a time-series impervious surfaces data from 1985 to 2015. Bayesian Relevant Lifecourse exposure models examined the associations between childhood greenspace availability and adolescent mental health and tested for critical/sensitive age periods. Generalised Estimating Equation logistic regression models assessed the associations between greenspace availability and mental health across adulthood. These analyses were adjusted for various important individual, family, and area-level covariates. Results: No associations were found between childhood greenspace availability and any adolescent mental health conditions. However, in adulthood, a one standard deviation increase in greenspace availability within 1500m and 2000m buffers was associated with a 12% and 13% reduced risk of depressive symptoms, respectively, after adjusting for various covariates. Discussion: This study supports the protective effects of greenspace on adult depressive symptoms, highlighting the significance of employing a spatial lifecourse epidemiology framework to examine the long-term effects of environmental factors on health over the lifecourse.